What are effective treatments for tinea capitis in children?. Issue 5 (May 2018) - Niedermier, Valerie; Hill‐Daniel, Jamie; Haver, Amy
Abstract : EVIDENCE‐BASED ANSWER : Systemic terbinafine and griseofulvin are both effective in reaching clinical and mycological cure as monotherapy in children with tinea capitis. Terbinafine is more effective for Trichophyton tonsurans, but griseofulvin is more effective for Microsporum species (SOR: A, meta‐analysis of RCTs). Adding either selenium sulfide shampoo or ciclopirox shampoo to griseofulvin results in similar high cure rates but the effect compared with griseofulvin alone is not known (No SOR given). Topical squalamine ointment is not an effective cure, resulting only in some hair regrowth (SOR: B, single, small RCT).